Oralidade e escrita: a presença do discurso reportado em entrevistas jornalísticas - Gomes, Flavia Elizabeth de Oliveira (2009)
In this work, we intend to discuss results from a research about retextualization in gender journalistic interview, considering speech dialogical approach. Retextualization activity, which implies the production of a new text through one or more basic texts, shows the presence of reported speech as an integral unit of discursive construction. Our corpus had been extracted from a section called Nossos Valores [Our Values], present at the syndical newspaper Adurn Notícias [Adurn News], from Federal University of Rio Grande do Norte (Brazil), which weekly publishes journalistic interviews with active professors from this institution. We describe retextualised text structure by correlating it to the one from the oral text, in order to identify and describe quoted speech, as well as features of the gender in which it is inserted. It was verified that, when it comes to reported speech present in the published interviews, which are representative of the research corpus, diverse incorporation procedures of alien property‟s speech take place, especially those regarding about reported speech use. The waterish presence of the other present in dialoged texts speech transformed in monologue texts demonstrates that there is not a clear demarcation among voices in certain parts of the written text. This is confirmed during analyses of the two interview versions, in which it is not always possible to distinguish the authorship of certain propositions, which in some way can point to Bakhtin‟s concept of intentional hybridity. Beyond Bakhtin‟s contributions (1990; 2000), the theoretical principles of this work are based upon Marcuschi (1986; 1999; 2001), Matencio (2003), Authier-Revuz (1982), and Favero et al. (1997; 1998; 1999; 2000)